Estimating the Employment and GDP Multiplier of Emergency Cash Transfers in Brazil - Cunha, Daniel (IMF Working Papers; Working Paper ;, 2022)
We estimate the subnational employment and GDP multiplier of Brazil's 2020 federal cash transfers to vulnerable households. Using two-stage least squares regressions we estimate a formal employment multiplier and then apply an analytical transformation to recover an implied GDP multiplier in the range of 0.5-1.5. The lower bound of this range lies below most estimates in the literature, which may result from the exceptional constraints imposed by the pandemic on supply chains and consumption. Nevertheless, even using the lower end of our range implies that federal cash transfers played an important role in supporting employment and GDP.